Special School as One of the Implementers of Education for Sustainable Development of Persons with Moderate and Severe Intellectual Disability, as well as Multiple Disability - WENDREŃSKA, IWONA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Iwona Wendreńska, Special school as one of the implementers of education for sustainable development of persons with moderate and severe intellec-tual disability, as well as multiple disability. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 163–180. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.08 The basis for choosing the subject of this article was the conviction that due to the recent expansion of the meaning of the term “sustainable development”, the essence of education for sustainable development, its objectives and tasks implemented in different types of schools, including special schools, are also subject to change. The article will present the results of research covering, on the one hand, the analysis of strategic and programme documents and, on the other hand, the results of surveys conducted among 164 teachers employed in special education institutions in the Silesian and Lublin Voivodships.